2018
DOI: 10.1021/acs.iecr.8b02928
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Alternating Thickened–Unthickened Gas Flooding for Enhanced Oil Recovery

Abstract: Direct gas thickening is a conventional mobility control method to improve volumetric sweep efficiency for miscible gas injection (MGI) projects. However, the viability of this approach with technically feasible thickeners has not been verified at the field-scale due to a combination of high costs and/or environmental issues. One approach to make this technique economically more attractive is the implementation of an alternating injection scheme (similar to water-alternating-gas (WAG)) that would require less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One would expect a greater increase because the PVEE molecular weight is greater than the PMO molecular weight, but a 3-fold viscosity increase at the same dilute mass concentration is unexpectedly high given typical dilute solution viscosity results. Further, in earlier work 23,24 Al Hinai and coworkers reported that CO 2 was thickened by 50% using 1.5 wt % P1D oligomer (MW 544). The same group conducted core studies that demonstrated how the alternating injection of thickened CO 2 with unthickened natural gas gave comparable results to the continuous injection of thickened natural gas.…”
Section: Introduction To the Need For Thickened Co 2 During Enhanced ...mentioning
confidence: 91%
See 3 more Smart Citations
“…One would expect a greater increase because the PVEE molecular weight is greater than the PMO molecular weight, but a 3-fold viscosity increase at the same dilute mass concentration is unexpectedly high given typical dilute solution viscosity results. Further, in earlier work 23,24 Al Hinai and coworkers reported that CO 2 was thickened by 50% using 1.5 wt % P1D oligomer (MW 544). The same group conducted core studies that demonstrated how the alternating injection of thickened CO 2 with unthickened natural gas gave comparable results to the continuous injection of thickened natural gas.…”
Section: Introduction To the Need For Thickened Co 2 During Enhanced ...mentioning
confidence: 91%
“…For example, 2 wt % CO 2 -soluble poly­(vinyl acetate) (PVAc; MW 11,000) was able to induce only a several percent increase in CO 2 viscosity at very high pressure . Al Hinai and colleagues examined the CO 2 -thickening ability of four low molecular weight polymers (P1D; MW 900; PVEE, MW 3800; poly­(isobutyl vinyl ether) (PIVE), MW 4000; PDMS, MW 5180), some of which Heller had previously found to be poor thickeners. They accurately portrayed the controversy regarding the viscous changes associated with these oligomers and low molecular weight polymers and reported viscosity increases significantly higher than those reported by Heller, yet much smaller than those shown in Zhang’s report .…”
Section: Introduction To the Need For Thickened Co2 During Enhanced O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thermodynamic miscibility is a critical state that has attracted a great deal of attention in many practical applications, such as pharmaceutical dosage forms, macromolecule materials, oil and gas production, etc. In practice, the miscibility state is defined as a stable homogeneous mixture that exhibits macroscopic physicochemical properties of a single-phase fluid .…”
Section: Introductionmentioning
confidence: 99%